2016
DOI: 10.4136/ambi-agua.1770
|View full text |Cite
|
Sign up to set email alerts
|

Análise da renovação das águas do Sistema Estuarino de Santos usando modelagem computacional

Abstract: A investigação de processos inerentes a um sistema estuarino permite inferir de forma mais precisa sua complexa dinâmica, possibilitando o balizamento de estratégias de ação em planos de gestão e projetos ambientais em regiões costeiras. Este trabalho apresenta um estudo da hidrodinâmica do Sistema Estuarino de Santos (SP), com enfoque na análise da renovação de suas águas, pelo efeito da maré e pelas vazões fluviais afluentes. Por meio do SisBaHiA® (Sistema Base de Hidrodinâmica Ambiental) foi implementado um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 5 publications
(5 reference statements)
1
7
0
4
Order By: Relevance
“…For instance, a study carried out in an estuarine system of Santos Basin (SP), showed the presence of saline plume. The referred author simulated Rt behavior [84] and estimated a value close to 30 days; therefore, when Rt value was compared to results in the present research, such value was relatively close to that of the estuarine system in Santos Basin at the dry period (November); of the period presenting lower rainfall and of the period when there was greater oceanic tide influence over upstream Amazonian estuary. In other words, saltwater is potentially more influential in the estuary at this period [10].…”
Section: Discussionsupporting
confidence: 78%
“…For instance, a study carried out in an estuarine system of Santos Basin (SP), showed the presence of saline plume. The referred author simulated Rt behavior [84] and estimated a value close to 30 days; therefore, when Rt value was compared to results in the present research, such value was relatively close to that of the estuarine system in Santos Basin at the dry period (November); of the period presenting lower rainfall and of the period when there was greater oceanic tide influence over upstream Amazonian estuary. In other words, saltwater is potentially more influential in the estuary at this period [10].…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, in developing countries, due to the high rate of urban occupation associated with technological deficiencies and public mismanagement, the discharge of sanitary effluents is one of the most concerning sources of pollution in coastal water bodies (MIRANDA; CASTRO; KJERFVE, 2002;DSIKOWITZKY et al, 2016;ROVERSI et al, 2016;WETZ et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…No intervalo de 510 a 780 minutos o SisBAHIA mostrou-se também bastante promissor na simulação real da altura de maré. Observou-se neste intervalo uma concordância entre o ICH e o SisBAHIA, mostrando mais uma vez a potencialidade de simulação de níveis de maré pela ICH, tendo em vista que o SisBAHIA é um software bem conceituado nacionalmente pela literatura especializada em cálculos hidrodinâmicos (FEITOSA et al, 2013;ROVERSI et al, 2016).…”
Section: Resultados E Discussão Comparação E Potencialidade Da Ichunclassified